Defeat of winter wheat plants in root rot, depending on agrotechnical measures - Тищенко, М. В.; Смірних, В. М.; Філоненко, С. В.; Ляшенко, В. В. (Scientific Progress & Innovations, 2018)
As a result of field studies, the effect of predecessors, fertilizer systems and methods of basic tillage on the damage of winter wheat plants by root rot in short-rotation crop rotations in the zone of inadequate moisture was established. The most affected wheat plants of winter rot was found in grain sown crop rotation, where the forerunner was the wheat itself, as well as in the grain-para-breeding crop rotation, where the black pairs were the precursor. The least affected by root rot of winter wheat plants (15.3–20.0 %) at the lowest intensity of disease (5.8–7.3 %) was observed after corn silage. Conducting surface cultivation of soil at a depth of 10–12 cm under grain crops, including under winter wheat, against the background of 6.25 t of manure + N33.8R45.0K33.8 + straw + gill in the crop rotation after corn on silage caused most defeat of wheat plants by root rot (24.4 %) with an increase in the intensity of the disease to a value of 10.5 %. Providing plowing for all crops in the fertile crop rotation for rotation of crop rotation per hectare of arable land of 6.25 tons of manure + N33.8R45.0K33.8 + straw + lace ensured the highest yield of wheat of winter wheat – 4.39 tons/ha.